Description of Mutual Cooperation Character through Curriculum Merdeka Teaching Module at Jatinegara 01 State Kindergarten - Yulia Indrawati; Nita Priyanti (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Mutual cooperation is a significant value in Indonesian society, and it includes the spirit of cooperation, mutual help, care, tolerance, and solidarity. In education, it is important to teach and shape the character of mutual cooperation in children from an early age. This study aims to describe the character of mutual cooperation through the use of the Merdeka Curriculum teaching module at Jatinegara 01 State Kindergarten. The research method used is descriptive qualitative with two groups of informant subjects: teachers as educators and students as material recipients. Data were collected through interviews, observations, and documentation studies of three teachers and learning activities for two weeks. The results showed that the Merdeka Curriculum teaching module effectively shaped the character of mutual cooperation in early childhood at Jatinegara 01 State Kindergarten. This study concludes that using the Merdeka Curriculum teaching module at Jatinegara 01 State Kindergarten positively impacts the development of mutual cooperation character in early childhood. The practical implication is the importance of developing interesting teaching modules that focus on building mutual cooperation in early childhood education institutions.